Social Issues in Management - Frederick, William C. (Academy of Management Review, 1976)
The article reviews several books pertaining to social issues in management, including “Private Management and Public Policy,” by Lee E. Preston and James E. Post, “The Corporate Dilemma,” by Dow Votaw and S. Prakash Sethi, and “The Value Issue of Business,” by Alvar O. Elbing and Carol J. Elbing.